2018
DOI: 10.1111/eth.12767
|View full text |Cite
|
Sign up to set email alerts
|

Limited flexibility in female Pacific field cricket (Teleogryllus oceanicus) exploratory behaviors in response to perceived social environment

Abstract: How populations adapt, or not, to rapid evolution of sexual signals has important implications for population viability, but is difficult to assess due to the paucity of examples of sexual signals evolving in real time. In Hawaiian populations of the Pacific field cricket (Teleogryllus oceanicus), selection from a deadly parasitoid fly has driven the rapid loss of a male acoustic signal, calling song, that females use to locate and evaluate potential mates. In this newly quiet environment where many males are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It is unclear why the sexes would differ in reproductive physiological plasticity, but other studies have also found sex-specific differences following the spread of flatwing in Kauai. For instance, Kauai females show less socially-induced plasticity in gene expression (Pascoal et al, 2018) and walking behaviors (Balenger & Zuk, 2015;Heinen-Kay, Strub, & Zuk, 2018) than males.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why the sexes would differ in reproductive physiological plasticity, but other studies have also found sex-specific differences following the spread of flatwing in Kauai. For instance, Kauai females show less socially-induced plasticity in gene expression (Pascoal et al, 2018) and walking behaviors (Balenger & Zuk, 2015;Heinen-Kay, Strub, & Zuk, 2018) than males.…”
Section: Discussionmentioning
confidence: 99%
“…Males from Kauai also walk around more when raised in the absence of calling song, which should increase the likelihood of a chance encounter with a female or calling male (Balenger and Zuk, 2015). As noted above, females reared in a song-less environment are also more phonotactic and express lower mating thresholds Swanger and Zuk, 2015), though they do not show similar flexibility in exploratory behaviors (Heinen-Kay et al, 2018).…”
Section: Alternative Mating Tactics and Behavioral Flexibilitymentioning
confidence: 99%